MATHEMATICAL MODEL OF THE INFLUENCE OF A GYMNAST: MATHEMATICAL MODEL OF THE INFLUENCE OF A GYMNAST - Rayimberdiyeva, Dilrabo; nabidjanova, Nargiza; Ismailov, Nurulla (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
This article discusses the impact of various forces that can arise during the movement of athletic girls in gymnastics clothes, the study of the stress-strain state, the types of fabric used for clothing, and the mathematical model of the force acting on it. Information about the values of the coefficients determined as a result of the actions is also discussed and highlighted.